Presence of Spontaneous Pain and Comorbid Pain Conditions Identifies Vulvodynia Subgroups. Issue 1 (January 2016) - Reed, Barbara D.; Plegue, Melissa A.; Williams, David A.; Sen, Ananda
Abstract : Objective: The aims of the study were to define the heterogeneity of vulvodynia by determining data-driven subgroups within the vulvodynia diagnosis using exploratory cluster analysis and to characterize the subgroups identified. Materials and Methods: Included were participants in the longitudinal population-based study of vulvodynia in southeast Michigan who screened positive for vulvodynia at least once during the study. A cluster analysis using variables reflecting vulvar pain characteristics and comorbid pain conditions was conducted. Variables reflecting best separation of clusters were used to assign participants to subgroup categories. Demographic, psychiatric, general health, and other vulvar pain characteristics were summarized for each subgroup, followed by multinomial regression and pairwise comparisons of subgroups on these factors. Results: Of 441 women screening positive for vulvodynia during the course of the study, 393 were eligible on the basis of data requirements. Cluster analysis suggested that best subgroup separation was based on the following 2 variables: (1) presence or absence of spontaneous vulvar pain and (2) presence or absence of other comorbid pain conditions. Subgroups did not differ by age or ethnicity. The subgroup having spontaneous pain and other comorbid conditions demonstrated greatest morbidity in general health measures, psychiatric disorders, and other vulvar pain measures. Primary versus secondary vulvodynia did not vary between subgroups and did not assist in subgroup separation in the cluster analysis. Discussion: Subgroups based on exploratory cluster analysis demonstrated that presence of spontaneous pain and the presence of comorbid pain conditions resulted in best separation of groups. Presence of both spontaneous pain and other comorbid pain conditions identified the group with greatest morbidity. Abstract : Presence of spontaneous pain and of other comorbid pain conditions identifies subgroups of differing morbidity among women with vulvodynia